THE EFFECTS OF COLD SHOWERS ON HEALTH – A REVIEW OF THE SCIENTIFIC LITERATURE - Michał Ziemba; Filip Jaroszewicz; Katarzyna Giedzicz; Rafał Kulgawczuk; Jan Smusz (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Cold water immersion (CWI), increasingly practiced through activities such as wild swimming, triathlon, and winter swimming, has gained attention for its potential health benefits. Recent scientific studies are beginning to substantiate traditional claims, indicating that regular cold exposure may yield positive physiological and psychological outcomes. These effects are mediated through both shivering and non-shivering thermogenesis, involving muscle activity and brown adipose tissue, which contribute to thermal homeostasis and may underpin longer-term adaptive health benefits. Aim: The aim of this review paper is to evaluate the effects of cold showers on physical and mental health. Materials and methods: A review of literature available in databases like PubMed, Google Scholar, Scopus and Web of Science conducted, using keywords including "cold showers", "health benefits", "immune system" Summary: This review examines current research on the health effects of cold showers, focusing on immunity, cardiovascular health, mood, metabolism, and post-exercise recovery. Evidence suggests cold showers may enhance immune function, improve mood, increase metabolic rate, and support muscle recovery. However, cold exposure can pose risks for individuals with cardiovascular conditions, such as arrhythmias or hypertension. While the benefits are promising, further clinical studies are needed to confirm long-term effects and identify safe, effective protocols for different populations. Conclusions: Regular cold showers may offer health benefits such as improved immunity, enhanced mood, and metabolic support. They can acutely raise blood pressure but may contribute to long-term cardiovascular regulation. Psychological and analgesic effects are likely mediated by sympathetic activation and hormonal responses. Despite promising findings, more rigorous studies are needed to confirm efficacy and safety across diverse populations.